Information System for Decision Support in the Field of Tourism Based on the Use of Spatio-Temporal Data Analysis - Baranova, V.; Orlenko, O.; Vitiuk, A.; Yakimenko-Tereschenko, N.; Lyashenko, V. (WARSE, 2020)
Information plays an important role in decision-making processes. The methods of data processing and analysis are of particular importance. Such methods should provide additional information. This is critical in decision support information systems. We propose to use wavelet coherence for spatio-temporal data analysis. This approach is considered for data from the tourism sector to assess the effectiveness of the decisions made. Calculations are given for real data. Hidden shortcomings in tourism are shown.
Keywords: Information System; Decision Support